Correction of a typographical error in Bignonia ‘ghorta’ (Bignoniaceae) - Madhukar, Virendra K.; Bandyopadhyay, Subir (Phytotaxa, 2017)
Wallich (1828–1849) published the work entitled “A numerical list of dried specimens of plants, in the East India Company’s Museum collected under the superintendence of Dr. Wallich of the Company’s botanic garden at Calcutta.” This work was lithographed from a manuscript written by N. Wallich and G. Bentham and has been often cited as “Wallich’s Catalogue.” This catalogue includes more than 8600 names, but lacks descriptions or references to the descriptions. As such, most of the names listed are nomina nuda and not validly published names (see Art. 38.2 Ex.1 of ICN, McNeill & al. 2012). Many of these nomina nuda were validated by Don (1831–1838).